Discurso Testimonial en la novela “Hasta no verte Jesús mío” de Elena Poniatowska - Guamán Aranda, Dayana Doménica (2024)
The purpose of the following work is to identify and understand how the testimonial discourse is represented in the novel “Hasta no verte Jesús mio” by the author Elena Poniatowska. To identify the characteristics of the novel-testimony, the theory developed by Miguel Barnet is applied, which allows this work to be differentiated from other literary creations. The type of testimonial discourse present in the novel is pseudo-testimonial, because it is invaded by the mediator. Language becomes an important element in this type of novels, in this case colloquialisms, vulgarisms, proverbs and informal speech are captured here. The enunciation is also included, which allows us to recognize the three voices that give life to this novel: interviewer (Elena Poniatowska), witness (Josefina Bórquez) and the literary character (Jesusa Palancares). The writer uses testimonial discourse to address important events in Mexican history, to give a voice to the marginalized and to raise awareness of social problems of the time.